Total anthocyanin content in intact açaí (euterpe oleracea mart.) and juçara (euterpe edulis mart.) fruit predicted by near infrared spectroscopy - Teixeira, Gustavo H. de A. [UNESP]; Lopes, Valquiria G.; Junior, Lu´Is C. Cunha; Pessoa, Josè D. C. (My University, 2015)
Açaı (Euterpe oleraceae Mart.) and jucxara (Euterpe edulis Mart.) palms are native to Brazil and these species are rich in anthocynanins. The methods applied to determine anthocyanins are time-consuming, generate chemical residues, and do not fit in modern on-line grading machines. As near infrared (NIR) spectroscopy has been used as a nondestructive method to determine anthocyanin, the objective of this study was to use NIR spectroscopy to predict total anthocyanin (TA) in intact açaı and juçara fruits. Spectra were collected using a Fourier transform (FT)-NIR spectrophotometer in the diffuse reflectance (4,000–10,000 cm-1) and TA reference data were obtained using the Association of Official Analytical Chemists (AOAC) method. Different treatments were applied to spectra and spectral data sets were correlated with TA by using partial least squares (PLSs) regression algorithm. The global-PLS model obtained with açaı and jucxara spectra resulted in a root mean standard error of prediction (RMSEP) of 10.05 g·kg-1. However, this model was not adequate for TA levels found in açaı fruits, therefore individual models were developed. The açaı-PLS model proved to be more adequate, as RMSEP was reduced to 3.56 g·kg-1. On the other hand, the RMSEP obtained with the juçara-PLS model (6.59 g·kg-1) was almost the same of the global model. NIR spectroscopy can be used to adequately predict TA content in intact açaı and juçara fruits and this method could be used as an analytical procedure to monitor their quality.
Keywords: Chemometrics; Nondestructive methods; Noninvasive methods; PLS; Postharvest; Quality